Synthetic fuel production from shredded scrap waste - Barragán-Gutiérrez, Iván Ernesto; López-Díaz, Alfonso; Krumm, Wolfgang (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This technological innovation project involved material identification, and design, installation, implementation, and evaluation of a pilot plant with capacity of 10 t per batch to recover materials and produce synthetic fuels (oil, syngas and solid) from shredded scrap waste. The results showed the proper way to separate materials (metals, and organic and inert compounds), and to perform the pyrolysis process to produce gas, oil, and coke as synthetic fuels from organic waste. The process started with the physicochemical characterization of the waste, followed by the selection of separation, sorting and processing technologies, and the definition of pyrolysis process parameters. Finally, the synthetic fuels were characterized, and uses for the furnace billet, ladle preheating, internal combustion engines, and auto generation were suggested. The results showed 82 % recovery of magnetic and non-magnetic metals, and production of synthetic fuels with PCI between 20 650 and 36 900 kJ/kg.